The Impact of Job Satisfaction and Role Conflict on Turnover Intention of Bakti Timah Nurses - Muchtadin; Zelvy Emmelya Sundary (Journal of Applied Management and Business, 2023)
Turnover intention causes increased costs for health organizations and reduces nurse performance. The research is aimed at knowing the impact of job satisfaction and role conflict on turnover intention. Respondents were 91 nurses at the Bakti Timah Pangkal Pinang hospital who were taken by purposive sampling method. The research design is quantitative causality with the data analysis method, namely PLS SEM. The results of the study found that job satisfaction has a negative impact on turnover intention, while role conflict has a positive impact on turnover intention. Future researchers can use the mediation of work engagement, work stress, and commitment to explain the weak relationship between variables.